Exploring the Potential of Soil Microbes as Biofertilizer Agents to Enhance Soil Fertility and Crop Productivity - Oktaviani; Pamela; Markus Patiung (Agriculture Journal, 2024)
The potential of soil microbes as biofertilizer agents to enhance soil fertility and crop productivity has garnered increasing attention in recent years. This study investigates the role of various soil microorganisms, including bacteria, fungi, and actinomycetes, in promoting plant growth and improving soil health. By examining the mechanisms through which these microbes contribute to nutrient cycling, nitrogen fixation, and phytohormone production, we aim to understand their impact on crop yields and soil properties. Field trials conducted in diverse agricultural settings demonstrate that the application of microbial biofertilizers can lead to significant improvements in crop productivity and soil fertility. The findings suggest that incorporating soil microbes into sustainable agricultural practices could be a viable strategy to reduce dependency on chemical fertilizers and enhance long-term soil health